2016
DOI: 10.1177/0961203316651739
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous lupus erythematosus and systemic lupus erythematosus are associated with clinically significant cardiovascular risk: a Danish nationwide cohort study

Abstract: Systemic lupus erythematosus (SLE) is a well-known cardiovascular risk factor. Less is known about cutaneous lupus erythematosus (CLE) and the risk of developing cardiovascular disease (CVD). Therefore, we investigated the risk of mortality and adverse cardiovascular events in patients diagnosed with SLE and CLE. We conducted a cohort study of the entire Danish population aged ≥ 18 and ≤ 100 years, followed from 1997 to 2011 by individual-level linkage of nationwide registries. Multivariable adjusted Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…The reason for the increased risk of depression in patients with SLE remains unclear. This is probably due to both direct and indirect consequences of the disease; a direct consequence of the systemic inflammation and an indirect consequence of the psychological burden of having and coping with a chronic disease . Previous studies have shown that depression is associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the increased risk of depression in patients with SLE remains unclear. This is probably due to both direct and indirect consequences of the disease; a direct consequence of the systemic inflammation and an indirect consequence of the psychological burden of having and coping with a chronic disease . Previous studies have shown that depression is associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, especially in recent years, evaluating the significant accompanying comorbidities in terms of morbidity and mortality such as CVDs and cerebrovascular accidents (which are more frequent in SLE) has been highlighted in skin-restricted lupus patients [46]. However, it is unknown that whether CLE is associated with risk of MetS or not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a large case-control study performed by Hesselvig et al in Danish population, significantly increased risk of CVDs and all-cause mortality were observed both in CLE and in SLE patients including inpatients and outpatients, as being higher in SLE, and these risks were found more significant in the patients with an age of ≤50 years [4]. In a Swedish study, Zöller et al examined whether there was an association between hospital admission for CLE and subsequent risk of hospitalization for coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations